Physiological predictors of a super-sprint triathlon performance in junior and U23 triathletes - Poffé, C.; Robberechts, R.; Kusters, M.; Weber, S.; Van Schuylenbergh, R. (Journal of Science and Cycling, 2025)
The mixed-team super-sprint triathlon relay (~300m swimming, ~6.6km cycling and ~1.5km running) performed in teams of four athletes, is the newest Olympic triathlon discipline. Until today, no scientific data is available on the specific physiological attributes. Our study aims to predict a super-sprint triathlon performance from physiological exercise testing. Fourteen national level triathletes performed physiological tests in swimming and running and competed in a super-sprint triathlon. The physiological profile in swimming and running was calculated and applied to predict triathlon performance. The speed at VO2max_swim corresponded well to the swimming speed during the triathlon (0.013 m·s-1, n.s.), whereas the running speed was similar to the running speed at metabolic steady state (MMSSrun) (0.05 m·s-1, n.s.). Stepwise multiple regression analysis selected MMSSrun as the primary predictor of triathlon performance (r2 = 0.66, p<0.05). The swimming speed at metabolic steady state (MMSSswim) (r2 = 0.84, p<0.05) and the amount of work that can be performed above MMSSrun (W`run) were also included in the prediction model (r2 = 0.91, p<0.05). Our data indicate that MMSSrun, MSSswim, and W`run allow for a precise prediction of a super-sprint triathlon performance. This information can be used to optimize training and pacing strategies.